PEMBERDAYAAN PELAKU UMKM PANGAN MELALUI SOSIALISASI DAN PENDAMPINGAN SERTIFIKASI HALAL DI TULUNGAGUNG - Fatwa Adhma Khoiri; Doni Fitriyanto; Triestina Melani (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2025)
This community service activity aims to enhance the understanding and capability of food-sector Micro, Small, and Medium Enterprises (MSMEs) in Tulungagung Regency in applying for halal certification. This activity uses the Asset-Based Community Development (ABCD) approach, focusing on empowering MSME food communities by identifying existing assets, building networks, and providing training. The program took place from August to October 2024 and included socialization and assistance sessions. Through the socialization phase, participants gained knowledge about Halal Product Assurance (HPA) policies, regulations, Islamic Sharia requirements, ingredient knowledge, and halal production processes. During the assistance phase, participants were facilitated in submitting a self-declared halal certification application. Evaluation results showed a significant increase in participant understanding, from an average of 34.7% to 85.1%. Additionally, some MSME actors succeeded in obtaining halal certificates through self-declaration facilitation. These results are expected to improve the competitiveness of MSME food products in both local and national markets and expand market access. Future activities are recommended to expand the scope of regular certification facilitation for other micro-enterprises to support the growth of a sharia-based economy in Indonesia.